The Role of the Faculty of Islamic Sciences at Sulaimani University in Enhancing and Educating the Will of its Students - Najma, Assistant Prof. Dr. Amide Muhammad Najma; Rashid, Assistant Prof. Dr. Mohsen Jalal Rashid; Said, Assistant Prof. Dr. Zana Muhammad Amin Said (Sulaimani Journal for Humanities, 2026)
No moral reform can be achieved without first cultivating the will. When we urge students to strive for learning instead of succumbing to ignorance, or to have good morals instead of negative qualities, such advice loses its value unless it is preceded by a strong will that enables them to apply what they see as good and avoid what they think is harmful. Repeated advice and counseling will be useless if the advisee is not able to control himself through his strong will. In this context, the College of Islamic Sciences plays a crucial role in educating its students intellectually and spiritually, by enhancing their ability to make conscious and thoughtful mental decisions based on ethical values. The importance of this research stems from the role of the College of Islamic Sciences in the development of willpower education in its students, with the aim of preparing them to become good citizens and positive contributors to their society. This research aims to explore the role of the College of Islamic Sciences in developing and promoting willpower education, with a focus on the college's interest in this field among its students, highlighting the strengths and weaknesses of this interest. The findings of the research can be of great benefit to those concerned at the College of Islamic Sciences in particular and the University of Sulaymaniyah in general, as it highlights the effectiveness of the college in raising the willpower of its students.
Keywords: Role of the College; Sulaymaniyah University; Promotion; Education; Willpower